Urgency of Policy Changes in Domestic Official Travel Costs in Order to Improve the Quality of Public Services in Mahakam Ulu Regency - Gregorius Lasah Higang (Dinasti Research, 2024)
The mechanism for financing official travel was changed to at cost for regional officials and a lump sum for regional legislative members through the issuance of Presidential Regulation No. 53 of 2023 as an amendment to Presidential Regulation No. 33 of 2020 concerning National Unit Price Standards. Pros and cons may arise with this policy. Putting that aside, the urgency of the issuance of Presidential Regulation No. 53 of 2023 for improving the quality of public services is an interesting thing to study as a form of sustainability of the bureaucratic reform agenda launched by the government. Moreover, this urgency becomes more interesting if contextualized with Mahakam Ulu Regency, which incidentally is a border area that is synonymous with the complexity of providing public services. This article aims to analyze the urgency of changing domestic official travel costs policies in order to improve the quality of public services in Mahakam Ulu Regency. A qualitative approach was applied by reviewing many relevant documents. The results of the analysis show that the quality of public services shows the urgency to be improved in Mahakam Ulu Regency due to the low HDI, high development inequality, and the implementation of bureaucratic reform which is still not optimal, thus affecting the quality of public services provided. In the new mechanism for official travel costs, the quality of public services in Mahakam Ulu Regency will be affected because it is related to the increased motivation of official travel agents to go directly into the community so that they know the real and comprehensive needs of the community, increased feedback (feed back) community towards the implementation of various Mahakam Ulu Regency Government programs thereby improving the quality of public services because of the precise improvements made, policy proposal initiatives originating from regional legislative members are much more oriented towards the interests of the community, minimizing corrupt practices, increasing budget efficiency in the delivery of public services, and increasing accountability and transparency in the implementation of public services.